Konvergensi IFRS di Indonesia: Analisis Dampak terhadap Manajemen Laba dan Transparansi Laporan Keuangan - Yusuf, Muh. Fathir Maulid; Ilham Akbar Garusu; Dian Mayafaty Rauf (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The convergence of International Financial Reporting Standards (IFRS) in Indonesia has become a crucial policy in improving the quality of financial reporting and attracting global investors. However, the effectiveness of this convergence in curbing earnings management and enhancing transparency remains debatable, with empirical findings varying across sectors and corporate governance conditions. This study employs a systematic literature review using thematic synthesis and the PRISMA protocol to integrate various credible sources, including Scopus, Web of Science, SSRN-indexed journals, OJK regulatory reports, and international accounting textbooks. The findings indicate that IFRS positively influences transparency, particularly in firms audited by Big Four auditors, with high institutional ownership and ERP-based technologies. Nevertheless, earnings management practices persist, especially in the property sector and family-owned firms. Factors such as audit quality, corporate governance, operational complexity, and local paternalistic culture moderate the effectiveness of IFRS implementation. Additionally, limitations in PSAK standards for digital assets, regional disparities, and regulatory inconsistencies pose significant challenges. This study emphasizes the need for an adaptive approach to IFRS in developing countries and recommends regulatory harmonization and institutional capacity-building for more effective implementation.